Aerobic exercise improves clinical symptoms in people with Parkinson’s disease and its potential mechanism - Wei, Quanqing; Wang, Hui; Liu, Yuning; Wang, Fengli; Wu, Xin; Xu, Chuanying; Cui, Guiyun; Xiang, Jie (Frontiers in Neurology, 2025)
BackgroundAn increasing body of research has identified a correlation between dysbiosis of the intestinal microbiota and the onset and progression of Parkinson’s disease. Furthermore, aerobic exercise has been shown to positively influence the regulation of intestinal microbiota. This study aims to examine the effects of aerobic exercise on the clinical symptoms of people with Parkinson’s disease and the underlying mechanisms.MethodsTwenty-six participants engaged in 8 weeks moderate-intensity aerobic exercise. The outcomes include the World Movement Disorder Society Unified Parkinson’s Disease Comprehensive Rating Scale part III and so on. Concurrently, fecal and blood samples were collected from the subjects.ResultsAfter aerobic exercise, the MDS-UPDRS part III score decreased. There was a statistically significant increase in the relative abundance of Clostridia (p = 0.043) and Roseburia (p = 0.015). Diversity analysis revealed a statistically significant increase in both the Chao1 index and the Beta diversity index among people with Parkinson’s disease. Additionally, bile acid metabolic profiling indicated a significant reduction in fecal 7-ketolithocholic acid concentration in people with Parkinson’s disease. Serum levels of Taurochenodeoxycholic acid and Taurodeoxycholic acid were also decreased. T-cell factor assays demonstrated that the levels of the pro-inflammatory cytokines interleukin-1β and interleukin-8 decreased, while the level of the anti-inflammatory cytokine interleukin-4 increased.ConclusionAerobic exercise has been shown to enhance both motor and non-motor functions in people with Parkinson’s disease. The underlying mechanisms may involve the modulation of intestinal flora composition and diversity, bile acid metabolism, and inflammatory cytokine levels.